THE IMPACT OF COAL MINING ON WATER AROUND OKOBO AND ODAGBO AREA, ANKPA, NORTH-CENTRAL NIGERIA - Umoru, Charles Ile; Atodo, Ajuma Susan; Usman, Abdulrahman S.; Bitrus, Christiana (FUDMA JOURNAL OF SCIENCES, 2024)
This study evaluates how mining operations affect the Okobo and Odagbo populations' main sources of water in Kogi State, Nigeria. High turbidity levels were found in water samples taken from the streams, which serve as these communities' primary water sources. This impedes photosynthesis and endangers aquatic life. The elevated quantities of heavy metals, particularly iron and lead found in the water samples, exceeded the Nigerian Industrial Standard and the World Health Organisation's permissible limits for human consumption. The research draws attention to the possible health hazards connected to extended exposure to these tainted water sources. Isolating mine water runoff, putting water treatment technology into place, sprinkling water to minimise dust, and requiring mining corporations to enforce land reclamation rules are some of the recommendations for reducing pollution. This study emphasises the urgent need for comprehensive environmental impact assessments and the implementation of stricter regulations to safeguard water resources and the overall well-being of the affected communities.
Keywords: Coal; Pollution; Okobo; Odagbo; Heavy metals; North-central; Nigeria